Synergistic modulation mechanisms in electrodeposited high-performance Ni/MoS2 coatings: multi-field coupling of ultrasonic cavitation and in-situ abrasive SiC particle polishing - Zubair Akbar; Haibin Liu; Qi Zhou; Honggang Zhang (Ultrasonics Sonochemistry, 2025)
To address the challenges of deteriorated surface morphology and insufficient mechanical and tribological performance in Ni/MoS2 nanocomposite coatings, this study proposes a novel ultrasonic-assisted electrodeposition method coupled with in situ SiC abrasive particle polishing. This synergistic approach enables refined crystallization, enhanced particle dispersion, and dynamic surface smoothing by simultaneously introducing ultrasonic cavitation and hard-particle dynamics into the deposition environment. The experimental results demonstrate that under an optimized ultrasonic power density (18 W/cm2), the surface roughness of the Ni and Ni/MoS2 coatings is reduced by 41 % and 70 %, respectively. The microhardness increased 2.5-fold for Ni and 3.4-fold for Ni/MoS2 compared to the coatings fabricated without ultrasound and abrasive SiC particle treatment. Remarkably, the corresponding friction coefficients decrease to 0.2 and 0.1, respectively, with wear rates reduced by 60 % and 75 %, respectively. The self-lubricating MoS2 further contributed by forming a uniform lubricating film under the combined effect of ultrasound dispersion and abrasive SiC particle polishing. This work establishes a fundamental framework for multi-field synergistic modulation during electrodeposition, offering a versatile route for the fabrication of high-performance defect-suppressed coatings for micro/nanoscale precision components.